Safety evaluation and hypolipidemic effect of aqueous-ethanol and hot-water extracts from E Se tea in rats. (October 2021) - Yang, Meilian; Sun, Pengzhen; Fan, Zhifeng; Khan, Afsar; Xue, Qingwang; Wang, Yifen; Cao, Jianxin; Cheng, Guiguang
Abstract: E Se tea, processed by the fresh leaves of Malus toringoides (Rehd.) Hughes, is a traditional herbal tea with various human benefits. The present study was aimed to evaluate the toxicity and hypolipidemic effect of aqueous-ethanol extract (EE) and hot-water extract (WE) from E Se tea. Eight main chemical constituents in EE and WE were respectively identified and quantified by UHPLC-HRMS/MS. EE is rich in TPC and TFC, while WE had higher TPS content. Both EE and WE exhibited strong antioxidant activity with no significant difference. The acute toxicity study revealed that the LD50 values were higher than 5000 mg/kg, while both WE and EE had no significant adverse effect in rats by subacute toxicity assay. However, the triglyceride (TG) content in experiment groups (male) and highest doses groups (female) significantly decreased. Furthermore, the hypolipidemic effect of WE and EE were performed on high fat diet induced hyperlipidemic rats. The result exhibited that either WE or EE could effectively regulate lipid droplet accumulation in liver, and reduce the adipocyte size. These results demonstrated that these two extracts from E Se tea could be regarded as a potential functional dietary supplement in preventing and treating diet induced metabolic diseases. Graphical abstract: Image 1 Highlights: Different extracts of E Se tea exhibited equivalent antioxidant activities in vitro. The LD50 of two different extracts of E Se tea were greater than 5000 mg/kg body weight. E Se tea extracts can be regarded as practically non-toxic based on acute toxicity. E Se tea extracts presented no cumulative toxicity in rats for 28 days. E Se tea extracts may be a potential functional dietary supplement for hyperlipidemia.